Geochemical modelling of natural contaminants in groundwaters and their removal by membrane processes - Fuoco, Ilaria; Critelli, Salvatore; Apollaro, Carmine; Marini, Luigi; Bartolo, Gabriele; Figoli, Alberto; De Rosa, Rosanna (Università della Calabria, 2021)
The presence of harmful elements dissolved in groundwaters represents one of the main environmental issues of present times. The aim of my PhD Thesis was to study the rock-to-water release and the fate of some inorganic pollutants dissolved in the groundwaters of the Calabria Region, and sometimes in other Italian areas, as well as to select suitable membrane technologies for their removal based on the acquired geochemical knowledge. Taking into account the peculiar characteristics of the groundwaters of the Calabria Region, three elements were considered: arsenic (As), fluorine (F) and chromium (Cr). The salient results of my PhD studies are presented in this Thesis, which is organized in four self-consistent Chapters structured as follows. Chapter 1. Geochemical modelling of As and F release into the crystalline aquifers of the Calabria Region. This section has been devoted to understanding the water-rock interaction processes occurring in the crystalline aquifers of the Calabria Region. Three different reaction path modeling exercises of granite dissolution were performed, reconstructing the water-rock interaction processes which occur: (i) in shallow and relatively shallow crystalline aquifers in which no As and F anomalies were observed; (ii) in As-rich areas, coupling the reaction path modeling of granite dissolution with the simulation of the adsorption of dissolved As onto precipitating crystalline and amorphous hydrous ferric oxide (HFO); (iii) in deep crystalline aquifers where high F concentrations were detected. A total of 160 water samples discharging from the crystalline aquifers of the Calabria region were used to fix the boundary conditions as well as to validate the outcomes of geochemical modeling. The results of the three geochemical modeling exercises of granite dissolution are in agreement with the analytical data and, therefore, it is reasonable to assume that they reproduce satisfactorily the water-rock interaction processes occurring during the travel of meteoric waters from shallow to deep crystalline aquifers, hosted both in granite rocks without mineralizations and in mineralized granites. Moreover, based on the results of the geochemical survey, some As- and F- rich groundwaters were selected and used as feeds for the treatment tests. Some relevant results have been already published by Fuoco et al. (2021a). Chapter 2. Geochemical modelling of Cr(VI) release into the ophiolite aquifers of Italy. This section has been focused on the water-rock interaction processes occurring in the main ophiolite aquifers of Italy. The obtained results were already published by Apollaro et al. (2019a). Reaction path modelling of serpentinite dissolution was performed varying the Fe2O3/(FeO +Fe2O3) weight ratio of serpentine and reproducing the analytical concentrations of relevant solutes, including Cr(VI), in the Mg-HCO3 groundwaters hosted in the ophiolite aquifers of Italy. The occurrence of geogenic Cr(VI) in these groundwaters appears to be potentially controlled by the oxidation of trivalent Cr to the hexavalent redox state, driven by the reduction of trivalent Fe to the divalent redox state. In fact, trivalent Fe is the only oxidant present in suitable amounts in serpentinite rocks, and even serpentine contains high contents of trivalent Fe as proven by recent studies. In contrast, the generally accepted hypothesis that geogenic Cr(VI) in waters interacting with serpentinites is driven by the 2 reduction of trivalent and tetravalent Mn is questionable. To validate the outcomes of the geochemical modeling of serpentinite dissolution and rock-to-water release of Cr(VI), the redox state of Fe in serpentine minerals of different Italian areas was measured (see next section). Moreover, the water sample characterized by the highest concentration of Cr(VI) was selected for the treatment tests. Chapter 3. Determination of the iron redox state in serpentine minerals by using TEMEELS analysis and its environmental implications. This section has been addressed to determine the Fe3+/FeT ratio of the serpentine minerals hosted in five serpentinite samples coming from the main ophiolite areas of Italy, in order to validate the results of the geochemical modeling of serpentinite dissolution and rock-to-water release of hexavalent chromium (see previous section). The electron energy-loss spectroscopy (EELS) combined with transmission electron microscopy (TEM) was selected as most suitable analytical technique because it provides the highest spatial and energy resolution allowing to obtain a good qualitative and quantitative information on iron redox speciation compared to other analytical techniques. Ten site-specific TEM foils were prepared and analyzed in the laboratories of the GFZ German Research Centre for Geosciences, in Potsdam. It has not been the simple application of a well-established analytical technique, but rather a challenging study, because it has been necessary to develop a new spectra processing method and prove its validity. The performed analyses provided in-depth knowledge on nanoscale structures of the studied samples and showed that Fe3+ represents from 75 to 85 % (median values) of total iron. The obtained results provide further support to the hypothesis concerning the oxidation Cr(III) to Cr(VI) driven by the concurrent reduction of Fe(III) to Fe(II), as suggested by geochemical modeling (see previous section). Chapter 4. Application of membrane processes to remove As, F and Cr(VI) from contaminated groundwaters. This section has been devoted to the removal of As, F and Cr from polluted groundwaters by means of membrane processes. Relevant results have been already published by Figoli et al. (2020), Fuoco et al. (2020) and Fuoco et al. (2021b). The geochemical approach was used as strong-scientific tool for pre-selection of suitable remediation systems and the contaminated groundwaters were chosen from the previous data collections. Several type of commercial nanofiltration/reverse osmosis membranes, not already tested in the pertinent literature, were selected depending on the type of application. Their efficiency was evaluated in terms of arsenic, fluoride and chromium rejection, water production and feed composition. The other main ions that contribute to water chemistry were also taken into account to evaluate the possible intended use of the considered waters after the treatments. Satisfactory results were obtained for each specific case of contamination. Moreover, an innovative membrane with absorbent capacities against As(III) and As (V) species was developed and the preliminary results are quite promising. Summing up, the findings obtained in this work are useful for the understanding of the rock-to-water release of the chemical elements of interest and their fate in natural waters. Moreover, the treatment of natural As, F, and Cr-contaminated groundwaters improved the knowledge and the data availability for future scientific and application developments in similar geological settings worldwide.
Dottorato di Ricerca in Scienze ed Ingegneria per l'Ambiente, le Costruzioni e l'Energia. Ciclo XXXIII
Keywords: Arsenic; Chromium; Fluoride; Geochemical modelling; Water remediation